Epistles. Book II - Pliny, the Younger; Whitton, Christopher, 1979- (Cambridge : Cambridge University Press, 2013)
Pliny the Younger's nine-book Epistles is a masterpiece of Roman prose. Often mined as a historical and pedagogical sourcebook, this collection of 'private' letters is now finding recognition as a rich and rewarding work in its own right. The second book is a typically varied yet taut suite of miniatures, including among its twenty letters the trial of Marius Priscus and Pliny's famous portrait of his Laurentine villa. This edition, the first to address a complete book of Epistles in over a century, presents a Latin text together with an introduction and commentary intended for students, teachers and scholars. With clear linguistic explanations and full literary analysis, it invites readers to a fresh appreciation of Pliny's lettered art.
Epistles In Brief -- Pliny's World -- A Book Of Letters -- Prose D'art -- Rhythm -- Intertextuality -- Afterlife -- Transmission, Text, Indexes -- Ad Lectorem C.plini Caecili Secvndi Epistvlarvm Liber Secvndvs.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Pliny, -- the Younger -- Correspondence